The Incidence of Sanctions Against Employers of Illegal Aliens - Hill, John K.; Pearce, James E. (Journal of Political Economy, 1990)
This article assesses the significance of sanctions against employers of illegal aliens for resource allocation and income distribution in the United States. Data from the 1980 Census of Population are used to identify the industries likely to be monitored most closely by the immigration authorities. A general equilibrium incidence analysis then is carried out using alternative assumptions about the overall level of enforcement. Estimates are made of the effects sanctions will have on the real wages of legal U.S. workers.